Sulfoximidovinil trifluormetil cetonas. Obtenção e aplicação na síntese de azóis e azinas derivadas - Vezzosi, Renata Pivetta (2007)
This work describes the synthesis of a new series of 4-alkyl(aryl)-4-tetramethylenesulfoximide-1,1,1-trifluorobut-3-en-2-ones (5a-k) by the O,N-exchange reactions of ketones (1a-k) [CF3C(O)CH=CR1R, where R = OMe, OEt; R1 = H, Me, Ph, 4-MePh, 4-MeOPh, 4-BrPh, 4-ClPh, 4-FPh, 4-NO2Ph, 4,4 -Bifenil, 1-Naftil] with tetramethylenesulfoximide (4) in absence of solvent and with 65-97% yields. Subsequently, the preparation of a new series of a geminated heterocyclic system 3-aryl-5-trifluorometyl-7,8-dihydro-6H-thieno[2,1-f] [1,2]-thiazine 1-oxide (6c-k) derivatives (60-85% yields) by an intramolecular cyclocondensation reactions of enones employing potassium t-butoxide in diethyl ether as solvent, is also reported. In a subsequent step, the O,N-exchange reactions of 4,4-diethoxy-1,1,1-trifluoro-3-buten-2-one (1l) with S,S-dimethylsulfoximide (2), S-methyl-S-phenylsulfoximide (3) e tetramethylenesulfoximide (4), to obtain the corresponding acyclic compounds 4-ethoxy-4-sulfoximide-1,1,1-trifluoro-3-buten-2-one (5l-m) are described. Also, the application of compound 4-ethoxy-4-dimethylsulfoximide-1,1,1-trifluoro-3-buten-2-one (5l) to obtain S,S-dimethylsulfoximide substituted pyrazoles, isoxazoles and pyrimidine (8-18), is reported.